Polite Questioning in Students' WhatsApp Group Discussion (A Research on Discourse and Communication) - Resyadi, Herman; Suraidah, Ainun (Palakka : Media and Islamic Communication, 2021)
This research is under the discipline of Discourse Analysis. It focused to investigate the politeness used by students in social media, especially WhatsApp application. This research was consist of 20 students in one class at the Graduate Program of State University of Makassar. To collect the data, the researchers transcribed students' chat and discussion from the students' WhatsApp group discussion. This researcher was analyzed by using discourse analysis approach based on the politeness theory by Brown and Levinson (1987). The result of this research showed that students only use positive politeness in questioning to show closeness and respect to the other students in the WhatsApp group discussion.